2012
DOI: 10.1371/journal.pone.0050749
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Like Differentiation Potentials of Endometrial Side Population Cells as Revealed by a Newly Developed In Vivo Endometrial Stem Cell Assay

Abstract: BackgroundEndometrial stem/progenitor cells contribute to the cyclical regeneration of human endometrium throughout a woman's reproductive life. Although the candidate cell populations have been extensively studied, no consensus exists regarding which endometrial population represents the stem/progenitor cell fraction in terms of in vivo stem cell activity. We have previously reported that human endometrial side population cells (ESP), but not endometrial main population cells (EMP), exhibit stem cell-like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 32 publications
4
74
1
1
Order By: Relevance
“…Human endometrial SP cells formed glandular, stromal, and endothelial structures when transplanted under the kidney capsule of immunodeficient NOD/SCIDγ mice [45]. In vivo studies have also suggested that human endometrial SP cells may be able to differentiate to a smooth muscle cell-like phenotype [47]. Reconstitution of endothelial cells was not observed in other studies [43], which may result from the heterogeneity of SP cells.…”
Section: Stem Cells In Endometriummentioning
confidence: 96%
“…Human endometrial SP cells formed glandular, stromal, and endothelial structures when transplanted under the kidney capsule of immunodeficient NOD/SCIDγ mice [45]. In vivo studies have also suggested that human endometrial SP cells may be able to differentiate to a smooth muscle cell-like phenotype [47]. Reconstitution of endothelial cells was not observed in other studies [43], which may result from the heterogeneity of SP cells.…”
Section: Stem Cells In Endometriummentioning
confidence: 96%
“…48 In vivo assays have demonstrated that endometrial side population cells may be genuine stem cells. 40,42,49 These assays transplanted these cells under the renal capsules of immunodeficient ovariectomized mice administered oestradiol and progesterone for eight weeks who were subsequently subjected to nephrectomy. The results showed that all grafts reconstituted tissue similar to the endometrium under the renal capsules.…”
Section: Endometrial Mscs In Humansmentioning
confidence: 99%
“…The results showed that all grafts reconstituted tissue similar to the endometrium under the renal capsules. 49 …”
Section: Endometrial Mscs In Humansmentioning
confidence: 99%
“…Yapılan çalımalarda endometrial mezenkimal kök hücrelerin in vitro olarak kondrosit, [20] adiposit [21] ve hematopoetik [22] farklılama gösterebil-dikleri saptanmıtır. Yapılan bir baka çalımada endometrial mezenkimal kök hücrelerin insülin ve glukagon sekrete eden endodermal pankreatik hücrelere farklılabildikleri ve bu hücrelerin immün sistemi baskılanmı farelerde oluturulan diyabet modelinde kan ekerini düürdükleri tespit edilmitir.…”
Section: Endometr‹al Mezenk‹mal Kök Hücreler‹n Plast‹s‹te Kapas‹tes‹unclassified